Diatesis Pasif dalam Bahasa Arab: Kajian Tipologi Linguistik - az-Zahra, Namira; Nasution, Khairina; Basaria, Ida (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
This study aims to describe the system of passive diathesis in Arabic by highlighting the morphological forms that mark passive constructions and analyzing the relationship between morphological forms and syntactic structures. The research is grounded in Linguistic Typology theory Comrie and Morphosyntactic Diathesis theory Haspelmath. It employs a qualitative approach with a descriptive method through a library research design. The data sources consist of classical and modern Arabic texts, including the Qur’an, literary works, traditional Arabic grammar books (nahwu), and scholarly articles and books on Arabic linguistics. The data comprise sentences or clauses containing passive constructions (al-mabnī lil-majhūl), collected using the note-taking technique. The data were analyzed using the distributional method and the immediate constituent analysis (ICA) technique. The findings reveal that the passive diathesis in Arabic is formed through two main strategies: the synthetic and the analytic. The synthetic strategy is realized through internal vowel alternation within the verb, while the analytic strategy is expressed through constructions involving auxiliary verbs such as qāma and tamma, which have undergone grammaticalization. Syntactically, the formation of the passive diathesis is characterized by the omission of the active subject (fāʿil) and the promotion of the object to the subject position (nāʾib al-fāʿil). This phenomenon demonstrates the close interrelation between morphology and syntax in the Arabic diathesis system and indicates a typological shift from a synthetic to an analytic system as a form of grammatical innovation.